Satyavīra Śraddhānanda - Meghani, Zaverchand Kalidas, 1896-1947; Sraddhananda, Swami (SAMP early 20th-century Indian books project ;, 1927)
Chiefly biography of Swami Sraddhananda, 1857-1926, Arya-Samaj leader; comprises Ātma-kathā (his authobiography), p. 1-67, Uttara-carita (his biography, later life, edited), p. 68-110, and Rāmāyaṇanī rahasya kathā, p. 111-124.